Promotion in the Creative Industries: A Case Study of the Perspective of Micro and Small Business Owners from the Publishing Industry Subsector - Peter MIČÁK (Communications of International Proceedings, 2020)
This paper aims to describe the theoretical differences in the application of marketing in the creative industries compared to traditional sectors of the economy, and identify, through statistical analysis, factors affecting the perception and opinion of the representatives of companies on the importance of promotion for the company. This paper analyses the companies from the publishing industry, which is a subsector of the creative industries. The theoretical part of the paper is based on the research of secondary sources in the form of scientific articles. The analytical part establishes the research hypotheses and analyses the primary data obtained from questionnaires. These data are analysed by using correlation analysis. Due to the ordinal nature of the data, their distribution and quantity, the Kendall correlation coefficient, was chosen to evaluate the hypotheses. Based on the established hypotheses, the following variables have been found to have an impact on the respondent’s views on the importance of promotion for the company: the existence of the planning process, the number of employees, the achieved education of the respondent and the production of the tailor-made products. The age of the company does not have a demonstrable statistical correlation with the opinion on promotion in the company. The established hypotheses were evaluated in the article but considering the nature of the creative industries and their inhomogeneity, it is not possible to automatically assume that the results related to the publishing industry will automatically apply in other subsectors.
Keywords: Creative Industries; Publishing Industry; Promotion; Marketing of SMEs; Opinions on Marketing.